Pengaruh Inovasi Produk Terhadap Kenaikan Pendapatan pada UMKM Budidaya Jamur Tiram di Desa Bandar Labuhan Kec. Tanjung Morawa - Annisa Rizkia; Ova Novi Irama (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The purpose of this product innovation is to increase the income of Oyster Mushroom Cultivating UMKM in Bandar Labuhan Village, Tanjung Morawa District, this product innovation activity is very influential for UMKM due to an increase in income during the innovation of processed food products made from oyster mushrooms. There are many benefits in oyster mushrooms so that many people enjoy this preparation. The preparation is called “TORTILLA AYAM JAMUR”. Chicken Mushroom Tortilla has a taste that has been innovated from the taste of eastern food to Indonesian food. Mushroom Chicken Tortillas are not marketed anywhere yet so that makes this product the only one available. The methods used in this activity are: (1) Collection of problems faced by the owner (2) Finding the best solution for the situation at hand (3) Providing suggestions for innovating processed products from oyster mushrooms to increase income.